ANALISIS PENGARUH AKTIVITAS U-TURN TERHADAP KINERJA JALAN MENGGUNAKAN METODE PKJI 2023: (Studi Kasus: Jalan HZ. Mustofa Kota Tasikmalaya) - Silvia Febriyani, Ikke; Saepudin, Uu; Defiana, Yanti (Jurnal Ilmiah Teknik Sipil, 2025)
ABSTRACT The growth of motor vehicles in Indonesia each year has led to increasing traffic congestion, particularly on urban roads with high traffic intensity. One such example is HZ. Mustofa Street in Tasikmalaya City, which has U-turn facilities with high activity levels that potentially reduce road performance. This study aims to analyze the impact of U-turn activity on road performance based on the Indonesian Highway Capacity Manual (PKJI) 2023 and to formulate alternative treatments that can improve traffic flow. The research method used is a quantitative approach through traffic surveys and field observations. The collected data include road geometry, traffic volume, U-turn vehicle volume, side friction, queue length, and demographic data. The analysis was conducted by calculating road capacity, degree of saturation, travel speed, delay, and level of service (LoS). The analysis results show that U-turn activity at the two studied locations causes a decrease in average vehicle speed, an increase in queue length, and a decline in road service level from category C to E and D during peak hours. This indicates that HZ. Mustofa Street has already reached a high level of saturation. Simulated alternative treatments, such as relocation or partial closure of U-turns, were found to improve road performance by reducing delays and increasing average vehicle speed, thus raising the LoS to category D. Therefore, it can be concluded that U-turn activity significantly affects the performance of HZ. Mustofa Street in Tasikmalaya City. Rearranging U-turn locations and controlling roadside parking are recommended as improvement measures to enhance efficiency and traffic flow. Keywords : U-turn, road performance, PKJI 2023, level of service, Tasikmalaya.